Prey consumption by cetaceans reveals the importance of energy-rich food webs in the Bay of Biscay. (September 2018) - Spitz, J.; Ridoux, V.; Trites, A.W.; Laran, S.; Authier, M.
Highlights: Annual and seasonal energy and biomass removals by cetaceans in the Bay of Biscay. Estimates address interspecific differences in the cost of living of cetaceans. Estimates based on functional prey groups. Small energy-rich schooling fish are the key prey group in the Bay of Biscay. Energy-rich food webs are crucial to maintaining ecosystem functions and services. Abstract: Ecosystem-based management requires a clear understanding of marine ecosystem functioning, particularly the transfer of energy (consumption) to higher trophic levels. However, robust estimates of consumption are generally hampered by a dearth of data for predators (diet and abundance), and by methodological weaknesses. We undertook a comprehensive assessment of energy requirements and prey consumption for the 10 most abundant cetacean species in the Bay of Biscay (northeastern Atlantic Ocean, France) by combining recent data on their abundances from aerial surveys, and diets from stomach content analyses. We also incorporated functional considerations to group prey and address interspecific differences in the cost of living of cetaceans that are independent of body size. Species considered included harbour porpoise, common dolphins, striped dolphins, bottlenose dolphins, long-finned pilot whales, Risso's dolphins, sperm whales, Cuvier's beaked whales, minke whales and fin whales. We used Monte Carlo resampling methods to estimate annual and seasonal (winter and summer) consumption over the continental shelf and slope—and found that small toothed whale populations (which were much more abundant than other cetacean groups) required about twice as much resources as baleen whales and deep-diving toothed whales combined. Our results show that small energy-rich schooling fish are the key prey group sustaining a large part of the cetacean community in the Bay of Biscay. The biomass removal of small energy-rich schooling fish by cetaceans is 6 times higher than removals of all other prey groups. High quality nutritional resources appear to be crucial to sustaining cetaceans and maintaining ecosystem functions and services in the Bay of Biscay, and should be carefully monitored.